Benign Eyelid Lesions: Six Months Study - E Abbasi Shavvazi; Z Asadollahi; M Gohari; MR Besharati (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2013)
Introduction: Benign eyelid lesions are classified to infectious, inflammatory and tumoral lesions. The various number of these lesions is due to unique eyelid anatomical structure. Some lesions are simple and do not need any treatment but sometimes patients refer to ophthalmologists due to beauty or problems such as pain, swelling. The aim of our study is to investigate and compare the relative frequency of benign eyelid lesions in Shahid Sadoughi eye clinic as well as the private offices. Methods: This cross sectional six month study was done on 247 patients who referred to Shahid Sadoughi eye clinic and the private offices in 2011. They were examined by direct observation and slit lamp regardless of the cause. The information was gleaned by a questionnaire and the research data was analyzed by SPSS (ver.16). Results: we studied 247 patients including 84(34%) male and 163(6%) female). The mean age of the patients was 42.7 years. 60.2% of lesions were in upper lid and 39.8% were in lower lid. 51.2% of lesions were in right eye and 48.8% were in left eye. The most common eyelid lesions were papilloma (32.9%) nevus (21.9%) and chalazion (14.1%) respectively. Conclusion: Papilloma, nevus and chalazion are respectively the most common lesion in men and women. Benign lesions were more common in women located more in upper lid, though there was no statistically difference between right and left lid.